My Pilgrimage in Mission - Bevans, Stephen B. (International bulletin of mission research, 2019)
This article traces Steve Bevans's journey as a "global theologian," from his first encounters with "contextual theology" through his development as a theologian and missiologist at Catholic Theological Union, Chicago, and his membership in the World Council of Churches' Commission on World Mission and Evangelism.